Relationship Between Spinal Anesthesia Injection Speed and the Incidence of Hypotension in Patients Undergoing Cesarean Section - Mafazi, Fikri Alim; Novrinta, Donatila; Sasongko, Himawan (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background : The incidence of post-spinal hypotension in pregnancy is very high 50-85%. There have been many studies preventing hypotension but still considered unsatisfactory. Reducing the speed of injection of spinal anesthetic drugs can prevent hypotension, but still controversial.Objective : to determine the incidence of hypotension, onset of achieving sensory blocks, and the association of injection rate with the occurrence of post-spinal anesthetic hypotension.Methods: A Randomised Control Trial Study, including 48 patients underwent caesarean delivery who fulfil inclusion criteria. Samples were divided into fast and slow groups. Spinal anesthesia was given using hyperbaric bupivacain 0.5% of 10mg, Fentanyl 25mcg, and 100mcg morphine total volume of 3 cc. Group A received fast injection for 10 seconds, while group B for 30 seconds. The incidence of hypotension, onset of block and incidence of side effects after spinal anesthesia were recorded.Result : The incidence of hypotension in the fast group was 70.4%, while in slow group was 23.8%. There was a significant association between injection rate with post-spinal anesthetic hypotension (p = 0.004). Onset of Block T6 post-spinal anesthesia is faster in the fast group. Furthermore, there was no significant difference in nausea, vomiting, and chills between two groups.Conclusion: Slow injection rate may reduce the incidence of post-spinal anesthetic hypotension. However, the onset of sensory block was faster achieved with fast rate injection, with no difference in other side effects.